Technological game addiction and character strengths in adolescents - Çakır, Yaren; Turan, Nazan (Journal of Dependence, 2022)
Nowadays, it is stated that extreme and unnecessary usage of technology which is used in parallel with different purposes leads to technology addiction. Taking into account the studies conducted regarding the subject, it is considered that the adolescent population constitutes the riskiest group in terms of technology addiction. In addiction to this, character strengths become the protective function for adolescents, and it is seen that the determination of the risk factors and the preventive measure studies with removing risk factors are focused on aiming to prevent technology addiction in adolescents. In this context, the goal of this review is to attract attention to technological game addiction and character strengths in adolescents and to create awareness of mental health professionals in reducing technology addiction in adolescents.
Keywords: Adolescent; character; technological game addiction